Optimization of Zakat, Infaq and Shadaqah Punishment Through The Three Circles Model In Realizing Mustahik Welfare - Tiara, Mutiara Muslimah; Lemiyana; Chici Rima Putri Pratama (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2024)
Abstract: Realizing well-being is a state where individuals or groups of society seek to meet their material, spiritual, and social needs due to unmet requirements. This study aims to evaluate and optimize the distribution of Zakat, Infaq, and Shadaqah (ZIS) funds through the implementation of the Three Circles Model to achieve the well-being of mustahik at BAZNAS Kota Palembang. The Three Circles Model, developed by the Ministry of Religious Affairs of the Republic of Indonesia, integrates a holistic approach in ZIS fund management with a focus on three main areas: muzakki, amil, and mustahik, encompassing social, economic, and religious aspects. This research employs a mixed-methods approach, combining quantitative analysis of ZIS fund collection and distribution data with qualitative interviews with mustahik and amil at BAZNAS Kota Palembang. The findings indicate that during the first six months of 2024, BAZNAS Kota Palembang successfully collected a total of Rp3,968,830,416 in ZIS funds and allocated Rp2,645,040,148 to various programs, including